Profile and microbiological isolates of asymptomatic bacteriuria among pregnant women in Abakaliki, Nigeria - Onu, Fidelis Agwu (Infect Drug Resist, 2015)
BACKGROUND: Detecting and treating asymptomatic bacteriuria (ASB) prevents urinary tract infection and its consequences. The cost-effectiveness of routine screening for ASB in pregnancy is controversial. In populations with high prevalence, however, it is worthwhile and justifiable. AIM: To determine the profile, prevalence, microbiological isolates, and risk factors of ASB among booking antenatal clinic attendees in Abakaliki, Nigeria. MATERIALS AND METHODS: This was a cross-sectional study involving booking antenatal clinic attendees at the Federal Teaching Hospital, Abakaliki, who met the inclusion criteria. This study occurred between January and December, 2012. The midstream urine samples of these women were subjected to microscopy, culture, and sensitivity. RESULTS: A total of 300 randomly selected booking antenatal clinic attendees participated in the study; 74 of them had ASB, giving a prevalence of 24.7%. With the exception of rural residence, sociodemographic and obstetric characteristics did not influence the risk of ASB among the participants in this study. Staphylococcus aureus was the commonest organism isolated. The majority of the organisms were sensitive to ofloxacin and ceftriaxone. CONCLUSION: There is a high prevalence of ASB among pregnant women in Abakaliki. With the exception of rural dwelling, sociodemographic and obstetric characteristics did not significantly influence the risk of ASB among these pregnant women. Therefore, routine ASB screening of pregnant women is recommended in our environment.